A Correlation Study of Family Support and Adolescents’ Motivation in Participating the HPV Vaccination - Widiasih, Restuning; Kurniawati, Anastasya Peni; Hendrawati, Hendrawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The information on the significance of family support in relation to the adolescent motivation to participate in Human Papilloma Virus (HPV) vaccination, remains limited. This study aimed to investigate the correlation between family support and adolescents’ HPV vaccination motivation. This study was quantitative with a cross-sectional correlational design and proportionate stratified random sampling approach. 271 students from two state junior high schools in the capital city of Indonesia participated in this study. The instruments were family support and motivational on HPV vaccination questionnaires. Univariate analysis to measure family support was first applied, then bivariate analysis using the Spearman Rank test. The study found that 52% of female students had support from their families at a moderate level, 48.7% of students exhibited a high level of motivation, while 51.3% had a moderate-low motivation to participate in HPV vaccination. According to bivariate analysis, there is a correlation between family support and adolescent motivation with a p-value of 0.05 (0.001) and coefficient of 0.486. The results show there to be a positive correlation; the higher the level of family support, the better the motivation of young women to undergo HPV vaccination. However, the number of students with a low motivation for HPV vaccination remains high. The government should develop an innovative program with a more comprehensive target to increase the HPV vaccination rate in Indonesia.